Cyborg Figurations: Exploring the Intersections of Technology, Embodiment, Identity, and Ecology - Gill Haddow; Cecilia Åsberg; Federica Timeto (Tecnoscienza, 2023)
This cross-disciplinary exploration delves into the multifaceted intersections of technology, embodiment, identity, and ecology through the lens of cyborg knowing. The first contribution focuses on the vulnerabilities faced by individuals with implantable cardiac defibrillators (ICDs), emphasizing the crucial need for acclimatization strategies and agency in navigating their cybernetic embodiment as “everyday cyborg”. The second contribution critically examines cultural technologies revealing their role in perpetuating biases and advocates for interdisciplinary approaches, drawing on feminist STS and cyborg theory, to adaptively reshape societal constructs. Lastly, the third contribution envisions a comprehensive theory of cyberzoa that extends the cyborg figuration to encompass nonhuman animals, fostering a post-anthropocentric perspective and an ecologically attuned examination of power relations, exploitation, and symmetrical relationships. By engaging with the concept of the cyborg, these contributions shed light on the complex dynamics and transformative potentials inherent in the realm of technology for both human and nonhuman lives.